REPRESENTATION OF WOMEN IN ADVERTISING ON CONSUMER PURCHASE DECISIONS THROUGH BRAND IMAGE IN BEAUTY PRODUCTS - Angelina, Helen; Selamat, Frangky (Graduate Program of Universitas Tarumanagara, 2025)
The background of this study is to understand how gender representation in advertising can influence purchase decision through brand image. This study specifically aims to examine how gender stereotypes and female advertising affect customer purchase decisions by focusing on brand image as a mediating factor. This study is a descriptive studies with cross-sectional method. A total of 201 respondents were given a questionnaire by the researcher, who used a quantitative method. Respondents were given a questionnaire with a Likert scale (1-5) to capture their views on gender representation and its effects. SmartPLS version 4 was used for data processing. The sample of this study is women from Generation-Z born between 1997 and 2012, from upper-middle economic strata products who have bought cosmetics in Jakarta. The study findings shows that gender stereotypes, female advertising, and brand image each positively impact purchase decisions. Additionally, both gender stereotypes and female advertising were shown positively impact brand image. Moreover, brand image was confirmed to have a significant mediating effect between gender stereotypes, female advertising, and purchase decisions. These findings show the importance of gender representation in advertising and its influence on brand image and purchase decision, providing insights for brands to create a marketing strategy for their advertising campaigns.